The Importance of the Discovery of North Sea Oil in the Development of the SNP and the Scottish Nationalism - Djamila HOCINI (Revue des Sciences Humaines)
To date, researches are made on the establishment of the Scottish Parliament in 1999. This development in the Scottish nationalist movement had its roots in the post-Second World War especially with the flourish of the Scottish National Party in the 1960s. This study seeks to show to what extent the discovery of North Sea Oil was important in the development of the SNP as well as the Scottish nationalist movement. It also sheds light on the efforts made by the SNP to reach devolution and aims to explain how this discovery represented a turning point in the electoral performance of the party. The latter started its electoral campaign in the beginning of the 1970s.